2019
DOI: 10.1111/pbr.12771
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study for frost tolerance in rapeseed/canola (Brassica napus) under simulating freezing conditions

Abstract: | INTRODUC TI ONRapeseed/canola (Brassica napus L.) is one of the most important oilseed crops in the world and second to soybean (Foreign Agriculture Services, United States Department of Agriculture, National Agricultural Statistics Service, 2019). It is an amphidiploid (AACC, 2n = 4x = 38) and evolved through spontaneous interspecific hybridization followed by genome duplication, chromosome fission, fusion and rearrangements between two diploid species, B. rapa L. (AA, 2n = 2x = 20) and B. oleracea L. (CC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
(91 reference statements)
2
6
0
Order By: Relevance
“…To predict the functional insights of all DEGs, the MapMan pathway annotator was used for the metabolism overview of the DEGs. It was found that rapeseed responded to CS depending on the genetic background (Figures 4B-D), which is supported by previous reports (Lei et al, 2018;Zhang C. et al, 2019;Wrucke et al, 2020). A similar expression trend for up-and downregulated DEGs was mainly detected in the secondary metabolism, amino acids, lipids, cell wall, minor CHO, and light reaction pathways during the three comparisons.…”
Section: Analysis Based On Transcriptome Data Of C6 and C18 Under Cs Conditionssupporting
confidence: 89%
“…To predict the functional insights of all DEGs, the MapMan pathway annotator was used for the metabolism overview of the DEGs. It was found that rapeseed responded to CS depending on the genetic background (Figures 4B-D), which is supported by previous reports (Lei et al, 2018;Zhang C. et al, 2019;Wrucke et al, 2020). A similar expression trend for up-and downregulated DEGs was mainly detected in the secondary metabolism, amino acids, lipids, cell wall, minor CHO, and light reaction pathways during the three comparisons.…”
Section: Analysis Based On Transcriptome Data Of C6 and C18 Under Cs Conditionssupporting
confidence: 89%
“…There is one marker (S1_306342432) very near the significant locus on C02 for freezing tolerance under field conditions that has low p-values in experiment one for both 2-week damage scores and Fv/Fo at 7 days. Likewise, there is a cluster of markers mapping to chromosome C04 between 23,260,477 and 23,260,521 bp that are closely linked to a marker associated with freezing tolerance under growth chamber conditions that mapped to 23,256,454 bp in a previous study [56]. Thus, although we did not find any highly significant loci previously identified by earlier studies, our study provides some additional support for freezing tolerance loci identified in those studies.…”
Section: Comparison To Other Association Mapping Studies Identify Add...supporting
confidence: 69%
“…There are two markers that have fairly low p-values in experimental run 2 for visual damage scores and for experimental run 1 for Fv/Fo at 7 days that are within 50 kb of a marker on A03 at position 20,587,761 bp associated with freezing tolerance under simulated conditions [38]. There is also a cluster of markers within 150 kb of the significant marker on chromosome A07 at 13,505,270 bp, another cluster near the marker on chromosome A09 at 8,152,488 bp, and one more near the marker on A09 at position 8,867,241 bp that were significant in a GWAS study of freezing tolerance under growth chamber freezing conditions [56]. There is one marker (S1_306342432) very near the significant locus on C02 for freezing tolerance under field conditions that has low p-values in experiment one for both 2-week damage scores and Fv/Fo at 7 days.…”
Section: Comparison To Other Association Mapping Studies Identify Add...mentioning
confidence: 91%
“…Those regions might be suitable for selection to improve two or more desired traits, simultaneously, for example, to improve both abiotic stress response, seed component, and seed yield (A4:3.07–4.11 Mb). Several studies have already investigated on the co-location of QTLs from a different category of traits ( Shi et al, 2012 ; Zhao J. et al, 2012 ; Ding et al, 2014 ; Bouchet et al, 2016 ; Körber et al, 2016 ; Stein et al, 2017 ; Wan et al, 2017 ; Rahaman et al, 2018 ; Jan et al, 2019 ; Wrucke et al, 2019 ; Wu et al, 2019 ; Zhang K. et al, 2019 ). Those studies demonstrated the importance of analyzing multiple traits, at the same time, to target the loci for breeding cultivars with the most advantageous profile.…”
Section: Discussionmentioning
confidence: 99%